What you see is what you get? - Review article: Encounters with modern Ireland: a sociological chronicle, 1995-96 / Michel Peillon and Eamonn Slater (eds.). Dublin: Institute of Public Administration, 1998. - Torode, Brian; Peillon, Michel; Slater, Eamonn (Economic & Social Studies, 1999)
Time was when Sociology took a pride in the difficulty of its subject, ?society?, and book covers presented themselves accordingly. The cover of Breen et al. (1990) promises to focus ?on the relationship between the policies pursued by the state and the class structure of Ireland? and to show that ?the benefits of Ireland?s economic development have been very unevenly distributed, leading to a growing polarisation between social classes?. In case the bookshop browser should doubt the seriousness of these suggestions, the next paragraph warns that the book is the product of ten years of research, synthesising empirical and theoretical work, resulting in a comprehensive overview. The credentials of the authors ? ?Senior?, ?Officer?, and ?Professor? ? are clearly stated. In short the book is written to be cited. It is an authoritative statement, to be read by researchers and other professionals, for whom it aspires to provide an objective record of significant social change.
Keywords: Book review; Review article; Social classes; Economic development; Ireland